2010
DOI: 10.1186/1471-2229-10-144
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the amylose content of durum wheat through silencing of the SBEIIagenes

Abstract: BackgroundHigh amylose starch has attracted particular interest because of its correlation with the amount of Resistant Starch (RS) in food. RS plays a role similar to fibre with beneficial effects for human health, providing protection from several diseases such as colon cancer, diabetes, obesity, osteoporosis and cardiovascular diseases. Amylose content can be modified by a targeted manipulation of the starch biosynthetic pathway. In particular, the inactivation of the enzymes involved in amylopectin synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 66 publications
(70 reference statements)
7
105
1
1
Order By: Relevance
“…Wx-A1, SsI-1, SbeI-A, SbeIIa-A, SbeIIa-B, SSIII, AgpL (large subunit of AGPase), and Pho1 (alpha-1,4-glucan phosphorylase) transcript levels were increased in the SGP-1 double null lines. The up-regulation of starch biosynthetic genes after the elimination of a key enzyme has also been observed in bread wheat where SbeIIa was silenced using RNAi (Sestili et al, 2010b). Using qRT-PCT, Sestili et al (2010b) observed increases in Wx-1, SSIII, Iso1, and Ld1 transcripts but no increase for SsI, SSIIa, SbeIIb, or SbeI.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Wx-A1, SsI-1, SbeI-A, SbeIIa-A, SbeIIa-B, SSIII, AgpL (large subunit of AGPase), and Pho1 (alpha-1,4-glucan phosphorylase) transcript levels were increased in the SGP-1 double null lines. The up-regulation of starch biosynthetic genes after the elimination of a key enzyme has also been observed in bread wheat where SbeIIa was silenced using RNAi (Sestili et al, 2010b). Using qRT-PCT, Sestili et al (2010b) observed increases in Wx-1, SSIII, Iso1, and Ld1 transcripts but no increase for SsI, SSIIa, SbeIIb, or SbeI.…”
Section: Resultsmentioning
confidence: 78%
“…durum) cultivar 'Svevo' and hexaploid SGP-A1/B1 null lines (Yamamori and Endo, 1996) had an 89% increase in amylose content compared to Svevo (43.6% SGP-1 null vs 23% wild-type) as well as reduced binding of SGP-2 and SGP-3. Elimination of SbeIIa in durum through RNA interference also resulted in increased amylose ranging from þ29% to þ200% (24% wild-type vs. 31e75% SbeIIa RNAi lines) (Sestili et al, 2010b). The very high amylose results observed by Sestili et al (2010b) may not be due solely to SbeIIa expression reduction since SbeIIa mutants have amylose level increases similar to those of SSIIa mutations (28% sbeIIa versus 23% wild-type) (Hazard et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic wheat expressing the double strand RNA targeting SBEII-b did not display a significant increase in starch amylose content while RNAi silencing of SBEII-a resulted in an endosperm starch content with more than 70% amylose. Sestili et al (2010) followed the same strategy with two cultivars of tetraploid durum wheat (T. turgidum L. var. durum).…”
Section: Carbohydrate Engineeringmentioning
confidence: 99%
“…The alteration of starch quantity and quality can be achieved through the overexpression of some enzymes involved in starch synthesis [60], by mutations or RNAi technology, such as the inhibition of potato SSII, SSIII and GBSS [61], or the decrease in the expression of wheat BEIIa and BEIIb [62,63]. In this way, by affecting the catalytic activity of enzymes involved in the synthesis of amylose or amylopectin, it could be possible to obtain starches for different purposes.…”
Section: Altering the Composition And Amount Of Starch By Biotechnolomentioning
confidence: 99%